The Influence of Student Management on the Effectiveness of the Interest and Talent Development Program for Grade XI Science Students in Senior High Schools - Abdul Fattah Nasution; Salwa Nabila Damanik; Mawaddah Tun'nisa; Azra Humaira (Manajia: Journal of Education and Management, 2026)
This study aims to analyze the influence of student management on the effectiveness of the interest and talent development program for eleventh-grade science students in junior high schools. Student management is a crucial aspect of education, playing a role in planning, organizing, implementing, and supervising student activities, including the development of interests and talents. The research method used was a quantitative approach with a descriptive correlational design. The population in this study was all eleventh-grade science students, with a proportional sampling technique used. Data collection was conducted through questionnaires, observation, and documentation. Data analysis used simple regression statistical tests to determine the extent of student management's influence on the effectiveness of the interest and talent development program. The results showed that student management significantly influenced the effectiveness of the student interest and talent development program. This suggests that the better the implementation of student management, the more effective the interest and talent development program will be. Therefore, schools are expected to improve the quality of student management to support the optimal development of student potential.